2009
DOI: 10.1245/s10434-009-0381-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of High-Risk Stage II Colorectal Tumors by Combined Analysis of the NDRG1 Gene Expression and the Depth of Tumor Invasion

Abstract: The assessment of NDRG1 expression offers valuable prognostic information for patients with colorectal cancer, especially for those with stage II disease. We propose that NDRG1 expression level could be used to select patients with stage II disease who are at increased risk of unfavorable outcome, and who may benefit from adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 23 publications
6
44
1
Order By: Relevance
“…In addition, NDRG1 was found to be negatively correlated with tumor progression, while being positively correlated with better patient prognosis for a range of cancers, including those of the prostate, breast, colon, and pancreas (5,(11)(12)(13)16). Considering the potential therapeutic implications of utilizing NDRG1 as a molecular target for the treatment of cancer, the molecular mechanisms by which NDRG1 is able to exert its anti-cancer effects have recently become the subject of intense research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NDRG1 was found to be negatively correlated with tumor progression, while being positively correlated with better patient prognosis for a range of cancers, including those of the prostate, breast, colon, and pancreas (5,(11)(12)(13)16). Considering the potential therapeutic implications of utilizing NDRG1 as a molecular target for the treatment of cancer, the molecular mechanisms by which NDRG1 is able to exert its anti-cancer effects have recently become the subject of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies examining the prognosis of patients with these latter neoplasms demonstrated that those with higher NDRG1 levels had a significantly better outcome when compared with those with low NDRG1 levels (5,(11)(12)(13). Hence, NDRG1 is a promising prognostic indicator and molecular target for these cancers (14), which represent some of the most common and fatal neoplastic conditions.…”
mentioning
confidence: 99%
“…N-Myc downstream-regulated gene 1 (NDRG1), also named differentiation-related gene-1, is involved in the development of central nervous system (33). NDRG1 was reported as a differentiation marker of breast cancer (34) and prognosticates better survival in CRCs (35). The IFG1R was considered as another differentiation-related gene in lung adenocarcinoma (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have revealed controversial results for the manner of NDRG1 regulation by HIF-1α under hypoxia. Various of these studies reported a marked upregulation of the NDRG1 expression level under hypoxic conditions, whereas others have shown downregulated NDRG1 under the same conditions (8,(13)(14)(15)18,19,25). Consequently, the regulation of NDRG1 under hypoxia is highly complex and its cellular function is still a matter of debate.…”
Section: Time-and Oxygen-dependent Expression and Regulation Of Ndrg1mentioning
confidence: 99%
“…with unfavorable patient prognosis in glioma (13), colorectal cancer (14), esophageal squamous cell carcinoma (15), pancreatic ductal adenocarcinoma (16), prostate (17,18) and breast cancer (19).…”
Section: Time-and Oxygen-dependent Expression and Regulation Of Ndrg1mentioning
confidence: 99%